2019
DOI: 10.1186/s12896-019-0530-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved CRISPR/Cas9 gene editing by fluorescence activated cell sorting of green fluorescence protein tagged protoplasts

Abstract: Background CRISPR/Cas9 is widely used for precise genetic editing in various organisms. CRISPR/Cas9 editing may in many plants be hampered by the presence of complex and high ploidy genomes and inefficient or poorly controlled delivery of the CRISPR/Cas9 components to gamete cells or cells with regenerative potential. Optimized strategies and methods to overcome these challenges are therefore in demand. Results In this study we investigated the feasibility of improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 64 publications
(95 reference statements)
1
19
0
Order By: Relevance
“…During the preparation of the manuscript, the 2A peptide was reported to be used for fusing Cas9 and GFP in the protoplasts of Nicotiana benthamiana. Fluorescence-activated cell sorting (FACS)-mediated selection of GFPexpressed protoplasts has been shown to facilitate Cas9mediated mutation enrichment (Petersen et al 2019), which is consistent with our study showing that Cas9-P2A-GFP improves the selection of transgenic plants with a high editing efficiency. In addition to the Cas9-P2A-GFP construct used in this study, the P2A peptide may be widely used to coexpress multiple proteins in plants for various purposes.…”
Section: Coexpression Of Multiple Proteins Using 2a Peptidessupporting
confidence: 91%
“…During the preparation of the manuscript, the 2A peptide was reported to be used for fusing Cas9 and GFP in the protoplasts of Nicotiana benthamiana. Fluorescence-activated cell sorting (FACS)-mediated selection of GFPexpressed protoplasts has been shown to facilitate Cas9mediated mutation enrichment (Petersen et al 2019), which is consistent with our study showing that Cas9-P2A-GFP improves the selection of transgenic plants with a high editing efficiency. In addition to the Cas9-P2A-GFP construct used in this study, the P2A peptide may be widely used to coexpress multiple proteins in plants for various purposes.…”
Section: Coexpression Of Multiple Proteins Using 2a Peptidessupporting
confidence: 91%
“…The Indel Amplicon Analysis (IDAA) 10 technique allows for fast and direct assessment of insertions/deletions (indels), with a sensitivity down to + /−1 bp, without the need for in depth Sanger sequencing 11 . IDAA was recently used for editing scoring of protoplast cell populations 9 , and in the present study the use of IDAA was expanded and adapted to plants with complex genomes, such as potato, where it proved an efficient and fast tool for editing assessment.…”
Section: Introductionmentioning
confidence: 98%
“…High efficient CRISPR/Cas9 editing are in many plants complicated by the presence of complex and high ploidy genomes and inefficient or poorly controlled delivery of the CRISPR/Cas9 components to cells with regenerative potential. Fluorescence Activated Cell Sorting (FACS) of cells expressing GFP tagged CRISPR/Cas9 is regularly used for enrichment of edited cell populations in mammalian cell systems 8 and more recently also expanded to plant protoplast cells 9 . The Indel Amplicon Analysis (IDAA) 10 technique allows for fast and direct assessment of insertions/deletions (indels), with a sensitivity down to + /−1 bp, without the need for in depth Sanger sequencing 11 .…”
Section: Introductionmentioning
confidence: 99%
“…This is illustrated by editing of the granule bound starch synthase gene GBSS in Solanum tuberosum (potato) (Figure 6A , B ), a tetraploid organism, where GBSS furthermore is represented by three allelic variants. IDAA on wild-type protoplasts ( 144 , 145 ) can reveal the presence of the four alleles, as they can be distinguished by size in the GBSS gRNA target region (Figure 6C , upper panel). Editing of potato was achieved through delivery of CRISPR/Cas9 to protoplasts that were subsequently analysed by IDAA, which revealed that indels had been induced (Figure 6C , middle panel).…”
Section: Introductionmentioning
confidence: 99%